Long-term survival and clinical outcomes following direct-acting antiviral (DAA) treatment in HCV decompensated cirrhosis in Brazil: a real-world study - Pereira,Gustavo H. (2022)
Abstract Introduction The outcomes regarding portal hypertension-related complications and infections after HCV cure in decompensated cirrhosis are scarcely reported. We aimed to identify the predictors of survival and to evaluate the frequency of decompensation events of cirrhosis, including hepatocellular carcinoma (HCC), portal hypertension complications and infections in a cohort of decompensated cirrhotic with sustained virological response (SVR) in a real-world scenario. Patients and methods This was a prospective study in consecutive HCV-infected patients with decompensated cirrhosis who achieved SVR after direct-acting antiviral (DAA) treatment. At baseline, clinical and laboratory data were recorded. Patients were followed until development of outcomes regarding further decompensation, death, or liver transplant. A Cox-regression analysis was performed and survival curves were constructed using the Kaplan Mayer method. Results One hundred and thirty patients (age 60 ± 9 years, 64% female, 70% genotype 1) were included and followed-up through three years. SVR was associated with a lower prevalence of ascites and an improvement in Child-Pugh and MELD scores. One and three-year probability of transplant-free survival was 93% and 66%, respectively. Variables related to three-years survival were MELD < 11 (HR 1.24, 95% CI 1.13-1.37) and absence of ascites (HR 2.03, 95% CI 0.99-4.13) after the end of treatment (91% versus 37% in patients with ascites and a higher MELD, p< 0.001). Conclusions Decompensated cirrhotics with SVR and a low MELD without ascites have an excellent long-term prognosis. On the contrary, those with higher MELD and ascites have a low probability of survival even in the short term and might be evaluated for liver transplantation.